Context Sensitive Links Go to Holdings (0) Save to: Save the selected records to My EndNote Web library more options ERI - A framework for secure message delivery and offline viewing - Razali, , Ezmir Mohd; Ahmad, , Ismail; Rao, , G. S. V. R. Krishna (2006)
This paper presents a security framework for secure message delivery and offline message viewing of the electronic bills. This framework utilizes various encryption technologies to protect the content of the email that carries the confidential information.